OPTIMALISASI HARA IN SITU MELALUI INTEGRASI TANAMAN DAN TERNAK: Optimalisation of In Situ Nutrient through Crop and Livestock Integration - Haruna, Harsani; Rasbawati, Rasbawati (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
Scarcity of fertilizer is always a problem at the farm level because the level of dependence of farmers on fertilizer needs is very high. The need for fertilizer at the farmer level continues to increase over the years, this raises the problem of environmental pollution and also a decrease in soil quality. In addition, farmers' income is relatively low due to several factors, namely high production costs and low production, on the other hand, due to the limited land area. One solution to address this problem is through the integration of Crops and livestock systems. The purpose of this activity is to provide knowledge, training and assistance to farmers in maximizing the potential of agricultural livestock waste as compost in crop and livestock integration systems. The method of activity is carried out by field observations about the problems faced by farmers. The results of the activity can be concluded that partner farmers are able to utilize feces waste and animal feed into compost as a source of nutrition for plants, in a day farmers can produce 2.5 kg of compost from animal manure and feed from 2 goats so that in a year farmers can produce 912.5 kg of compost. In addition, partner farmers are also able to utilize the technology model of crop cohesiveness in maximizing the potential of land in conditions of limited land area. Previously, farmers only used one type of farming business, with this activity farmers could work on two or more types of farming in one land, so farmers could increase their income. Keywords: Integration, organic fertilizer, fertility, economy. ABSTRAK Kelangkaan pupuk selalu menjadi persoalan di tingkat petani karena tingkat ketergantungan petani akan kebutuhan pupuk sangatlah tinggi. Kebutuhan pupuk ditingkat petani semakin tahun teruslah meningkat, hal ini memunculkan persoalan pencemaran lingkungan dan juga penurunan kualitas tanah. Selain itu pendapatan petani relatip rendah karena beberapa faktor yakni biaya produksi tinggi dan produksi rendah disisi lain yakni karena faktor keterbatasan luas lahan. Salah satu solusi untuk menjawab persoalan tersebut yakni melalui sistem integrasi tanaman dan ternak. Tujuan kegiatan ini untuk memberikan pengetahuan, pelatihan dan pendampingan kepada petani dalam memaksimalkan potensi limbah pertanian peternakan sebagai kompos pada sistem integrasi tanaman dan ternak. Metode kegiatan dilakukan dengan observasi lapangan tentang permasalahan yang dihadapi oleh petani. Selanjutnya tahapan sosialisasi dan pelatihan dengan praktek langsung. Hasil Kegiatan dapat disimpulkan bahwa petani mitra mampu memanfaatkan limbah Feces dan pakan ternak menjadi kompos sebagai sumber nutrisi bagi tanaman, dalam sehari petani dapat menghasilkan kompos 2,5 kg limbah kotoran ternak dan pakan dari 2 ekor kambing sehingga dalam setahun petani dapat menghasilkan 912,5 kg kompos. Selain itu petani mitra juga mampu memanfaatkan teknologi model keterpaduan tanaman ternak dalam memaksimalkan potensi lahan dalam kondisi keterbatasan luasan lahan. Sebelumnya petani hanya memanfaatkan satu jenis usaha tani, dengan kegiatan ini petani dapat mengusahakan dua atau lebih jenis usaha tani dalam satu lahan, sehingga petani mampu meningkatkan penghasilan. Kata Kunci: Integrasi, pupuk organik, kesuburan, ekonomi.